Association of IL-6, IL-10 and TGF-β1 gene polymorphisms with brucellosis: A systematic review with meta-analysis. (October 2019) - Fu, Juan; He, Hong-Yan; Ojha, Suvash chandra; Shi, Han; Sun, Chang-Feng; Deng, Cun-Liang; Sheng, Yun-Jian
Abstract: Background: Brucellosis is one of the major public health problems worldwide. Several current studies have provided data that polymorphisms in the interleukin-6 (IL-6), interleukin-10 (IL-10) and transforming growth factor beta1(TGF-β1) gene were associated with the susceptibility to human brucellosis, but the results remain inconsistent. Objectives: The aim of present study was to investigate the relationship between IL-6 (−174 G/C), IL-10 (−1082 A/G, −819C/T) and TGF-β1 (codon 10, codon 25) gene polymorphisms and brucellosis. Methods: We performed a comprehensive search of the PubMed, EMBASE, Web of Science, OVID-EBMR, and the Cochrane Library up to Oct. 30, 2018. The search was designed using the following key words: "brucellosis" or" "brucella melitensis", "IL-10" or "interleukin10" or "interleukin-10", "IL-6" or "interleukin6" or "interleukin-6", "TGF-β1" or "TGF-beta1" or "transforming growth factor β1", "polymorphism" and "single nucleotide polymorphism (SNP)". Crude odds ratios (ORs) with 95% confidence intervals (CIs) were used to measure the strength of association between TGF-β1, IL-10 and IL-6 polymorphisms and brucellosis risk. All the statistical analyses were conducted by Review manager 5.3 software. Results: A total of 8 studies involving 1308 cases and 902 controls met the inclusion criteria for IL-6, IL-10, TGF-β1 polymorphisms and brucellosis risk. There was a slightly trend of increasing risk of brucellosis in individuals with the G allele compared with individuals with the C allele (OR = 1.07, 95% CI: 0.85–1.33, P = 0.57) in IL-6 polymorphism. However, statistical analysis showed that these differences are not significant. Our results suggested TGF-β1 (codon 25 G/C) GG genotype may be considered as a risk factor for brucellosis (OR = 1.67, 95% CI: 1.12–2.50, P = 0.01). Herein, we failed to find any significant association between IL-10 (−1082 A/G, −819C/T), TGF-β1 (codon 10C/T) gene polymorphism and susceptibility to brucellosis in all gene models. Conclusion: IL-6 (−174 G/C), IL-10 (−1082 A/G, −819C/T), and TGF-β1 (codon 10C/T) polymorphisms is not a risk factor for brucellosis infection. TGF-β1 codon 25 GG genotype may be considered as a risk factor for brucellosis. Highlights: Our study is the first meta-analysis about IL-6, IL-10 and TGF-β1 gene polymorphisms and the susceptibility of brucellosis. This study demonstrated that the TGF-β1 (codon 25G/C) GG genotype was associated with the susceptibility to brucellosis. Compared with the previous single research, the conclusions drawn are more evidence-based in present study.